Real-time MPEG-4 transmission over wireless LAN - Mohammed Jama, Abdirisaq; Khalifa, Othman Omran (IIUM Press, 2011)
Wireless systems based on IEEE802.11 technology became very affordable today, and allow end-users to connect to the network without cables. As most of multimedia devices have IEEE802.11 interface cards already built-in, or it can be added at very low cost, it seemsthat we have technology that fulfils our needs. Unfortunately these sounds too good to betrue, 802.11 b standard, with maximum physical data rate of II Mbps should be able to support Standard Definition (SO) MPEG-4 (Moving Picture Experts Group) encoded video stream, while faster 802.11 g/a networks (with 54 Mbps) support High Definition (HD) video stream. There is also relatively new standard, which is not officially released yet (only in draft version), IEEE802.11 n, with theoretical maximal throughput of 300 Mbps, but we are not evaluating this one, as it's not as popular as IEEE802.11 a/b/g yet.